Meningkatkan Pelayanan Publik Di Desa Banyuasin Kecamatan Banyuasin II dengan Sosialisasi dan Penyuluhan Tata Kelola Administrasi Desa - Wahyuli, Yofitri Heny; Helda Fitriani; Meitha Nella; Andela Anggleni (EDUPEDIA Publisher, 2023)
Socialization and counseling activities regarding village administrative governance are part of community service activities. The purpose of this socialization and counseling is to improve the ability or quality of the Marga Sungsang Pemdes village apparatus, especially in the field of administrative governance. The method used is socialization and counseling with dialogue or brainstorming techniques. With this activity, the performance and administrative capabilities of village staff and village officials as well as BUMDES managers in Marga Sungsang Village, Banyusin II District, Banyuasin Regency, will increase, so that it will change the traditional way of work into a professional way of working to improve community services.